PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI RANTAI MAKANAN DI KELAS V SD NEGERI OETONA - Atafani, Zamirah Atalia; Yudhawardhana, Hartoyo; Koro, Maxsel (Journal of Character and ELementary Education, 2024)
This research aims to improve science learning outcomes on food chain material through the use of the surrounding environment as a learning medium in class V of Oetona State Elementary School. The method used is Classroom Action Research through two cycles, each cycle consisting of 4 stages, such as planning, implementation, observation, and reflection. The data analysis technique used in this research is quantitative and qualitative descriptive. The results of this research in cycle I, the average student score was 55.66 with a completion percentage of 40%. In cycle II the students' average score increased to 86.33 with a completion percentage of 100%. Thus, the results of the research about Using the Surrounding Environment as a Learning Media to Improve Science Learning Outcomes are said to be successful because they have increased.